2017
DOI: 10.1038/s41598-017-03235-5
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolutionary history of freshwater Rhodophyta: further insights based on phylogenomic evidence

Abstract: Freshwater representatives of Rhodophyta were sampled and the complete chloroplast and mitochondrial genomes were determined. Characteristics of the chloroplast and mitochondrial genomes were analyzed and phylogenetic relationship of marine and freshwater Rhodophyta were reconstructed based on the organelle genomes. The freshwater member Compsopogon caeruleus was determined for the largest chloroplast genome among multicellular Rhodophyta up to now. Expansion and subsequent reduction of both the genome size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
2
24
2
1
Order By: Relevance
“…These results strongly contradict the statements by Nan et al. () that Batrachospermales and Thoreales are derived from the marine relative Palmaria palmata (Palmariales) ~415–484 mya. We therefore advocate that the inclusion of more taxa in Nemaliophycidae is critical to properly approach the issue in terms of the evolutionary transition from marine to freshwater habitats in the freshwater lineages including Batrachospermales, Thoreales, and Balbianiales.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…These results strongly contradict the statements by Nan et al. () that Batrachospermales and Thoreales are derived from the marine relative Palmaria palmata (Palmariales) ~415–484 mya. We therefore advocate that the inclusion of more taxa in Nemaliophycidae is critical to properly approach the issue in terms of the evolutionary transition from marine to freshwater habitats in the freshwater lineages including Batrachospermales, Thoreales, and Balbianiales.…”
Section: Discussioncontrasting
confidence: 91%
“…Yang et al (2016) showed these two orders as part of a large clade, with Batrachospermales diverging earlier (~330 mya) from a highly diverse group including the Thoreales and several orders including freshwater and marine representatives (e.g., Acrochaetiales, Balbianiales, and Nemaliales). These results strongly contradict the statements by Nan et al (2017) that Batrachospermales and Thoreales are derived from the marine relative Palmaria palmata (Palmariales) 415-484 mya. We therefore advocate that the inclusion of more taxa in Nemaliophycidae is critical to properly approach the issue in terms of the evolutionary transition from marine to freshwater habitats in the freshwater lineages including Batrachospermales, Thoreales, and Balbianiales.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Although there are some comprehensive studies on mt genomes for some groups of red algae (e.g. Yang et al 2016;Salomaki and Lane 2016), only two mt genomes were described for members of Batrachospermales so far: Sheathia arcuata by Nan et al (2017) and Lympha mucosa by Wolf et al (2017). This contrasts with the eight plastid genomes described for species of the order (Lee et al 2016;Nan et al 2017;Paiano et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…En Argentina son escasos los trabajos dedicados al estudio de este grupo de algas (Lazo, 1978;Gauna y Parodi, 2005;Daga, Soteras, Daniele, Dominguez, 2014), en especial las referidas a agua dulce. Usualmente, son componentes importantes de la ficoflora de ríos o arroyos, ya sea en términos de abundancia o distribución (Nan et al, 2017), tienen hábitos bentónicos y en comparación poseen menor tamaño que los miembros marinos (Sheath y Hambrook, 1990).…”
unclassified